Tantangan Pembelajaran Sekolah Dasar pada Masa Pandemi di SDIT Asdu - Anastasia, Anastasia; Azzahra, Aprilia; Nisa’, Diana Khoirun; Cendany, Nafisa Nuarista (ARZUSIN, 2022)
During the Covid-19 pandemic, the learning pattern changed from doing face-to-face learning, while now doing screen-to-screen in the form of zoom, google meetings or using WhatsApp as was done by teachers at SDIT ASDU, while some of them used limited face-to-face learning, giving rise to several challenges. But behind the regulations given by the government, of course, it aims to protect all Indonesian citizens, especially people who are very vulnerable to exposure to the Covid-19 virus such as small children and elderly people, but this time we will not only discuss learning problems that arise. only due to the pandemic but we will also discuss the solution. According to the dictionary of education, education itself is defined as follows: 1) the process of a person developing abilities, attitudes, and other behaviors in the society in which they live, 2) the social process that occurs in people who are exposed to selected and controlled environmental influences (especially those that affect them). come from school), so that they can obtain optimal development of social skills and individual abilities. In other words, education is influenced by the environment of the individual to produce changes that are permanent (permanent) in behavior, thoughts, and attitudes.